2020
DOI: 10.36680/j.itcon.2020.010
|View full text |Cite
|
Sign up to set email alerts
|

Technology acceptance model for Augmented Reality and Building Information Modeling integration in the construction industry

Abstract: The digitalization of the construction industry has immense potential for dramatically improving the industry’s practices. Concerning current measures in construction project management, the industry is still dependent on traditional construction methods. However, the application of fully automated techniques within the construction industry has not yet been a widespread practice. Thus, this may explain why there is a slow adaption of digital growth within the construction industry and specifically in developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 39 publications
(37 reference statements)
0
43
0
1
Order By: Relevance
“…Although some studies (Cai et al, 2015;Alaiad and Zhou, 2017) indicated that PEOU has a high effect on the acceptance of MR technology, Choi et al (2017) suggested comfortability as a measure of user acceptance. The same applies to the factor of perceived enjoyment which some studies indicated had a high effect on the acceptance of MRDT technologies ( € Ozgen et al, 2019;Elshafey et al, 2020) but this factor was not strongly supported by other scholars in the construction context (Choi et al, 2017;Pal et al, 2018). Although Jetter et al (2018) reported the insignificant effects of PU and PEOU on attitude, based on the review undertaken, there were moderate relationships among these paths.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although some studies (Cai et al, 2015;Alaiad and Zhou, 2017) indicated that PEOU has a high effect on the acceptance of MR technology, Choi et al (2017) suggested comfortability as a measure of user acceptance. The same applies to the factor of perceived enjoyment which some studies indicated had a high effect on the acceptance of MRDT technologies ( € Ozgen et al, 2019;Elshafey et al, 2020) but this factor was not strongly supported by other scholars in the construction context (Choi et al, 2017;Pal et al, 2018). Although Jetter et al (2018) reported the insignificant effects of PU and PEOU on attitude, based on the review undertaken, there were moderate relationships among these paths.…”
Section: Discussionmentioning
confidence: 93%
“…Results indicated that all the aforementioned constructs impacted upon BI with human detachment concerns being the strongest predictor of user adoption of WSN-SHHS. Elshafey et al (2020) investigated the acceptance of BIM and AR integration by construction industry practitioners. A literature review followed by a survey study were chosen as the instruments for conducting the research.…”
Section: Key Factors In Different Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these changes to be successful, they need to be accepted by the users of the Construction 4.0 technologies. This is achieved when users perceive the technologies as easy to use and easy to control (Elshafey et al, 2020). Then the users view these technologies as useful and have confidence using them.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst some relevant comprehensive literature reviews were conducted, scholars of these studies often adopt unique approaches in selecting and reviewing VR, AR and MR related publications, dependent upon their research purposes (Elshafey et al, 2020, Fenais et al, 2020. To state a few, Guo et al (2017) and Xiao et al (2018) focus on reviewing VR/AR in construction safety.…”
Section: Introductionmentioning
confidence: 99%